Healing the schism : Karl Barth, Franz Rosenzweig, and the new Jewish-Christian encounter - Rosner, Jennifer M. (Studies in historical & systematic theology., 2021)
"The past and future of Jewish-Christian dialogue The history of the relationship between Judaism and Christianity is storied and tragic. However, recent decades show promise as both parties reflect on their self-definitions and mutual contingency and consider possible ways forward. In Healing the Schism, Jennifer M. Rosner maps the new Jewish-Christian encounter from its origins in the early twentieth-century pioneers to its current representatives. Rosner first traces the thought of Karl Barth and Frank Rosenzweig and brings them into conversation. Rosner then outlines the reassessments and developments of post-Holocaust theological architects that moved the dialogue forward and set the stage for today. She considers the recent work of Messianic Jewish theologian Mark S. Kinzer and concludes by envisioning future possibilities. With clarity and rigor, Rosner offers a robust perspective of Judaism and Christianity that is post-supersessionist and theologically orthodox. Healing the Schism is essential reading for understanding the perils and promise of Messianic Jewish identity and Jewish-Christian theological conversation."--Publisher.